PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pinem, Fanny Br; Prima, Argo Putra (SCIENTIA JOURNAL, 2019)
Each organization has an objective to expand thriving for proprietors or investors with the goal that all organizations contend to build their benefits. Profit the board rehearses are completed by approved individuals, for example, directors and invested individuals in that. Past research results because of administrative possession and institutional proprietorship on income the executives are as yet the primary fascination for directing examination once more. The investigation means to rethink the impact of administrative possession and institutional proprietorship on profit the board recorded on the Indonesian stock trade. the assembling area and sub-areas that are utilized by products and utilization (buyer merchandise) are chosen as research tests. The test outcomes utilizing different direct relapse examination strategies demonstrate that administrative possession and institutional proprietorship contrarily influence profit the board. The aftereffects of this test demonstrate the low collection esteem with high administrative